Epidemiology of soil-transmitted helminths and Schistosoma mansoni: a base-line survey among school children, Ejaji, Ethiopia - Ibrahim, Temam; Zemene, Endalew; Asres, Yaregal; Seyoum, Dinberu; Tiruneh, Abebaw; Gedefaw, Lealem; Mekonnen, Zeleke (The Journal of Infection in Developing Countries, 2018)
Introduction: School children are among the high risk groups for soil-transmitted helminths (STHs) and Schistosoma mansoni (S. mansoni) infections in developing countries. The aim of this study was to determine the prevalence and associated factors of STHs and S. mansoni among primary school children. Methodology: A cross-sectional study was conducted from February 15 to March 30, 2016, involving a total of 340 primary school children (age range 6 to 19 years). Socio-demographic and related data were collected using interviewer-administered questionnaire. Stool samples were collected from each study participant and examined using direct wet mount and modified Kato-Katz thick smear technique. Intensity of the STHs and S. mansoni were determined by estimating the eggs per gram (EPG) of stool. Factors associated with STH and S. mansoni infections were analyzed using multivariable logistic regression model. Results: Prevalence of the STHs and S. mansoni were 38.2% and 12.94%, respectively. The main predictors of STH infections among the children studied were being in the age group of 16-19 years, untrimmed finger nail and household latrine unavailability. Moreover, male children, children with habit of swimming and bathing in the river had significantly higher odds of S. mansoni infection. Most of the children infected with the parasites had light infection. Conclusions: The burden of STHs and S. mansoni was high among the school children. Deworming intervention should be strengthened, along with awareness creation on proper disposal of human excreta and personal hygiene. Regular monitoring of the burden of the parasites and mass drug administration is required.